PERUBAHAN BENTUK PENYAJIAN TARI GUEL DI KABUPATEN ACEH TENGAH (KAJIAN SEJARAH) - Sari, Indah Nirmala; Syai, Ahmad; Hartati, Tengku (Jurnal Ilmiah Mahasiswa Sendratasik, 2017)
This research entitled The form transformation of Guel dance in Central Aceh District (Historical study). Meanwhile, the problem of this research is how the Guel Dance in Central Aceh District transforms in terms of the dance form. This research aims to describe the form transformation of this Guel dance. This research use a qualitative approach in form of descriptive analysis. The subject of this research is the Guel dances artist and Guel dancer as well. The object of this research is the form transformation of Guel dance in Central Aceh District. Technique of data collection in this research is done by observation to achieve a comprehensible image regarding the things being observed, an interview to seek the information deeply, and documentation which is done by investigating the belongings as well as pictures that can help the researcher in order to accomplish this research. The techniques of data analysis used are data reduction, data display, and conclusion drawing. The result of the research shows that Guel dance was originally presented as a tradition of welcoming the royal guests, this dance also presented in a certain families wedding parties. The Guel dance then had a change in form so it became the compulsory element that is presented in the Gayonese wedding celebration especially in the Central Aceh District and Bener Meriah. As the era keeps developing, the Guel dance has changed in terms of its form. Hence, this dance is widely presented for the purpose of entertaining and shown in a lot of art events among people in Central Aceh District. The Guel Dance is not changed specifically due to the fact that it still is the same in term of presentation, it only had a transformation in several parts such as the attire, musical instruments, and the number of the dancer. The Guel dance still show its originality by preserving the symbol of white elephant and Senggeda (didong) in its dance.Key words: Guel dance, form transformation